Sistem Akademik Pondok Pesantren Berbasis Website Menggunakan Laravel Studi Kasus Ponpes Al Fatah Komplek Dar El Hasani - Rizqi Nafisatus Sa'adah; Tri Haryanti; Heni Rahmawati (CV. ITTC INDONESIA, 2025)
Islamic boarding schools (pondok pesantren) are a distinctive form of education in Indonesia that have proven their independence since long ago. The rapid development of information technology has driven the need for a structured academic information system, including in Islamic boarding schools. Based on observations at Pondok Pesantren Al Fatah Komplek Dar El Hasani, Banjarnegara, the process of recording student data and payments was previously carried out manually in a ledger, resulting in time- consuming data retrieval and the risk of data loss. To address this issue, a web-based Academic Information System was developed using PHP programming language, MySQL database, and the Laravel framework. This system is designed to facilitate the input of student and teacher data, as well as to generate financial and student violation reports quickly and accurately. The system development uses the Waterfall method, which includes the stages of analysis, design, coding, testing, and maintenance. Research data were collected through observation, interviews, and literature studies. The results of the Black Box Testing show that the system functions as expected, and the Likert Scale assessment obtained a score of 88.94%, indicating that the system is feasible to be implemented in improving data management efficiency at Pondok Pesantren Al Fatah Komplek Dar El Hasani.